2017
DOI: 10.1021/acs.jced.7b00242
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Long Chain Alkylated Imidazolium Based Chloride and Bis(trifluoromethanesulfonyl)imide Ionic Liquids

Abstract: In this research synthesis, purification and characterization of six long-chain imidazolium based ionic liquids (ILs) including C 10 , C 12 , and C 14 alkyl chain with chloride and NTf 2 anions was investigated. All of these studied ILs were characterized using NMR, CHNSO, and DSC, and some impurities such as water, chloride, and metal contents were reported. The temperature dependence of some physicochemical properties such as density, dynamic and kinematic viscosity, refractive index, surface tension, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 85 publications
2
20
0
2
Order By: Relevance
“…Despite the fact that the IL is actually mixed with PO as co-binders for the preparation of the carbon paste, the previous trends correlate well with the conductivities and viscosities that the [ [38][39][40][41][42][43][44]. It is a wellknown fact that the conductivity and viscosity for many ILs are generally inversely related [51], thus the more viscous the ionic liquid, the lower the conductivity observed due to the decrease of the ion mobility [44,51].…”
Section: Effect Of Chain Length Of Alkyl Substituted Imidazolium Catimentioning
confidence: 84%
“…Despite the fact that the IL is actually mixed with PO as co-binders for the preparation of the carbon paste, the previous trends correlate well with the conductivities and viscosities that the [ [38][39][40][41][42][43][44]. It is a wellknown fact that the conductivity and viscosity for many ILs are generally inversely related [51], thus the more viscous the ionic liquid, the lower the conductivity observed due to the decrease of the ion mobility [44,51].…”
Section: Effect Of Chain Length Of Alkyl Substituted Imidazolium Catimentioning
confidence: 84%
“…The K­[C n C 1 Cp] data (circles) were measured in this work. The [C n C 1 Im]Cl data are averages from multiple sources, given in the Supporting Information.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Development of novel task specific ionic liquids designed by introducing various functional groups to cation has attracted much attention considering its applications. Many research groups have reported alkyl chain substituted ionic liquids and tested for LIBs . However, in this case, only the anions present in ionic liquid provides Li + ion coordination sites by forming solvation shell.…”
Section: Introductionmentioning
confidence: 95%